But My Child Speaks English: Native English Parents’ Perception on Mother Tongue as Medium of Instruction - Terogo, Ionell Jay; Calvo, Xin Xian; Canete, Kent Aryll; Cinco, Michael James (JPAIR Institutional Research, 2022)
The study delves into the perception of the parents of learners whose first language is English towards Mother Tongue-based Multilingual Education (MTBMLE). The questionnaire accumulates the perception of parents as important stakeholders in MTBMLE implementation to provide insight into family language policy in the Philippines. Native English speakers in this study refer to Filipino children who use English more comfortably than any other language at home in the Central Philippines region, with Sinugbuanong Binisaya as the local mother tongue. The study uses Personality Implicit Theory, Threshold Theory, and Sociocultural Theory to describe how these parents feel about their children’s mother tongue acquisition. Findings revealed that parents whose children are native English speakers agreed to the benefits of the mother tongue in the language and sociocultural development of the learners. Thus, native English speakers may unconsciously learn the language of the environment (Sinugbuanong Binisaya) when they converse and interact with the people of the said language. Moreover, seeking the perception of parents of Native English learners provides an important guide for any other institutions across the globe that have not implemented the MTBMLE fully as a subject to consider its implementation. It opens the possibility of training parents on an informed family language policy which assists children in learning MTBMLE, as they greatly help their children's language acquisition in the Cebuano language and appreciate the local culture.
Keywords: Education; MTB-MLE; perception; mother tongue; multilingual education